SARS-CoV-2 seroprevalence in a high-altitude setting in Peru: Adult population-based cross-sectional study - Huamaní C. (2021)
This study was supported by FONDECYT (Fondo Nacional de Ciencia y Tecnología, Peru), code: 071-2020. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.